Cancer incidence among Parkinson's disease patients in a 10-yrs time-window around disease onset: A large-scale cohort study. (July 2016) - Peretz, Chava; Gurel, Ron; Rozani, Violet; Gurevich, Tanya; El-Ad, Baruch; Tsamir, Judith; Giladi, Nir
Abstract: Objective: To compare the incidences of any cancer and specific types among patients with Parkinson's disease (PD) in a 10-yrs time window around diagnosis, to that of the general population. Methods: We conducted a population-based, retrospective large-scale cohort study on 7125 newly diagnosed PD patients who had just initiated anti-parkinsonian medications between 1.1.2000 and 12.31.2012; all members of Maccabi Health Services (MHS), a large Israeli HMO. Cancer incidence during the same period was collected from MHS cancer-registry. Standardized-Incidence-Ratio (SIR) accounting for age, chronological-year and sex were calculated to compare cancer risks of PD patients to that of MHS population. Results: The PD cohort (54% males) had a mean age at initiation of anti-parkinsonian medications of 71.2 ± 10.3years. In a time-window of 6.6 ± 3.4years before and 4.0 ± 3.9years after PD was first treated, 21% of the men and 15% of the women were diagnosed with incident-cancer. We found no-difference in any cancer risk for the PD cohort compared to the reference population: SIR = 0.99 (95%CI: 0.92–1.06) for males and 0.98 (95%CI: 0.89–1.07) for females. Risks for lung and colon cancers in the PD cohort were significantly lower for both sexes compared to the reference population. Risks for breast, central nervous system, kidney, leukemia, lymphoma, melanoma, ovarian, pancreatic, prostatic, rectal and thyroid were similar for the two populations. The SIRs did not differ between the sexes. Conclusions: We found no difference in the risk of any-type of cancer among PD patients compared to the general population, focusing on 10yrs time-window around the initiation of anti-parkinsonian medications. Highlights: The age and sex adjusted risk for new cancer of any type was similar between PD patients and the general population. PD patients had lower risks of new lung and colon cancers compared to the general population accounting for age and sex. The age and sex adjusted risk for new melanoma was similar between PD patients and the general population in both sexes.